The Coupling of Finite Element Method and Boundary Element Method for Two-Dimensional Helmholtz Equation in an Exterior Domain (Journal of Computational Mathematics, 1987)
This paper presents a new coupling of the finite element method and the boundary element method to solve the two-dimensional exterior Helmholtz problems by using the asymptotic radiation conditions in [1], in which the coupling relations are the same as C. Johnson and J. C. Nedelec's. The error estimates are derived and results of numerical calculation in comparison with analytic solution verify the theoretical estimates.